Advanced HCCI Engines: Challenges and Potential Applications - Xie Mingyang (E3S Web of Conferences)
Homogeneous Charge Compression Ignition (HCCI) engines are considered an emerging internal combustion technology with significant potential for enhancing fuel efficiency and lowering emissions compared to traditional Spark Ignition (SI) and Compression Ignition (CI) engines. By igniting a homogeneous air-fuel mixture through compression without the need for a spark plug, HCCI engines achieve a more uniform and complete combustion process, resulting in lower NOx and particulate matter (PM) emissions. Despite these advantages, challenges such as limited control over combustion timing, susceptibility to knocking, and the generation of unburned hydrocarbons have hindered widespread adoption. Recent advancements in engine control strategies and hybrid technologies offer promising solutions to these critical issues, potentially enabling broader application of HCCI engines in both the automotive industry and power generation sectors. As research continues to address these challenges, HCCI engines may play a pivotal role in the future of more ‘green’ internal combustion systems with higher efficiency.